Parents’ Perceptions on Parental Involvement in Their Children’s Education in Giyani Municipality Rural-based Schools, Limpopo Province, South Africa - Ngozwana, Nomazulu; Machobane, Amohelang; Chauke, Thulani; Lepholletse, Maphuthi (Australian and International Journal of Rural Education, 2024)
The importance of parental involvement in children’s education cannot be overemphasized. This study aimed to explore the role that parents play in the education of their children in the Giyani Municipality, Limpopo Province South Africa. The study followed Epstein's model of school-parent-community partnerships to understand the participation of parents in the education of their children. A qualitative approach was employed to guide the gathering and analysis of the data. Fifty-eight parents that were purposively selected from the four rural schools participated in the focus group discussions that were audio-recorded. Inductive qualitative thematic analysis was used, and the ethics were observed. The findings revealed the role of parental involvement in their children’s education as working with schools, home-schooling, modelling positive attitudes, emotional support, and career counselling. This study has implications for policy and practice in a parent-teacher relationship in rural schools by suggesting that parents should be involved in policy development such as when the curriculum changes.